Spatial relationships and interactions of immune cell niches are linked to the pathologic response of muscle-invasive bladder cancer to neoadjuvant therapy - Wasilijiang Wahafu; Quan Zhou; Xihua Yang; Yongming Yang; Yuanyuan Zhao; Zhu Wang; Xiangpeng Kang; Xiongjun Ye; Nianzeng Xing (Journal of Translational Medicine)
Abstract Background The identification of the complex spatial architecture of immune cell infiltration and its interaction mechanisms within tumor ecosystems provides crucial insights into therapeutic responses to neoadjuvant therapy in muscle-invasive bladder cancer (MIBC). This study aims to characterize the spatial features of distinct cell-type niches within the tumor microenvironment (TME) of patients with varying responses to neoadjuvant therapy. Methods We performed spatial transcriptomic profiling on six MIBC specimens obtained from a registered clinical trial (ChiCTR2000032359), generating whole-transcriptome spatial atlases to map the TME architecture. High-throughput analytical frameworks were employed to deconstruct the TME, and key findings were validated through immunohistochemistry and mouse model experiments. Results Our analysis revealed that tissues from complete responders exhibited greater infiltration of T and B cells, with the formation of tertiary lymphoid structure (TLS). Trajectory analysis identified CCL19/CCL21 as the key signaling molecules driving TLS formation in MIBC. Mouse experiments demonstrated that recombinant CCL19/CCL21 protein injections promoted intratumoral TLS formation and enhance the efficacy of immunotherapy. Furthermore, we observed significant intrinsic heterogeneity within individual tumors, which may contribute to the lack of therapeutic efficacy in MIBC. Conclusions This study underscores the critical role of TLS formation in the response to neoadjuvant therapy in MIBC. We identified CCL19/CCL21 as key drivers of TLS formation within MIBC tumors and potential immune-sensitizing agents. Additionally, the intrinsic heterogeneity of tumor should be considered a significant factor influencing therapeutic efficacy.